Socioeconomic Characterization, Identification and Prioritization of Major Constraints and Potentials in Tulu Harbuki Micro watershed, Lalo Kile District, Kellam Wollega, Oromia (Research in Agriculture Livestock and Fisheries, 2025)
In many Countries, watershed development plays a significant role in rural development and natural resource management plans. The baseline survey study is crucial to address biophysical and socioeconomic-related issues before CALM P4R implements its community-based participatory integrated watershed management program at a chosen watershed. The goal of the study was to evaluate the socioeconomic situation, potential, and constraints of the chosen watershed, to evaluate the biophysical data of the model watershed that was documented, and to prioritize issues for interventions in the model watershed that were indicated in the Tulu Harbuki Micro watershed for further improvements to promote sustainable and productive livelihood through the integration of different watershed components in a participatory approach. Household interview and biophysical resources assessment followed by watershed mapping techniques were used for the data collection. Purposive sampling methods were used to select 36 households in the watershed. Descriptive statistics by frequency distributions means and percentage and diversity indices were used for data analysis. The findings showed that problems with soil erosion, deforestation, and soil fertility, as well as termites, were the main causes of land degradation. Crop diseases and a lack of agricultural inputs (fertilizers and better varieties) were two of the area's biggest issues. The following interventions were suggested as part of the watershed management programs: Soil erosion control measures, soil fertility enhancement activities, SWC practices, the planting of niche-compatible multipurpose trees, home garden Agroforestry, and other treatments. Once more, participatory integrated learning should be used to increase rural communities' awareness of and capacity for integrating natural resource management technology for effective soil and water conservation measures.Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 363-382